Effect of Curcumin towards Metabolic Disturbance Parameters in Patient with PCOS: A Systematic Review and Meta-Analysis of Clinical and Preclinical Randomized Controlled Trials - Angeline Ekafentie; Nicolas Daniel Widjanarko; Yuliana Yosephine; Mutiara Riani (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2023)
Objective: Polycystic Ovarian Syndrome (PCOS) is a gynecologic and endocrine disorder with metabolic disturbances and infertility as the most common long-term consequences. Curcumin comes up as one of the alternative herbal remedies in PCOS treatment options. This study aimed to investigate the therapeutic effect of curcumin on metabolic disturbance parameters in PCOS patients and PCOS-modeled rats. Method: A systematic search of eligible studies was done using PubMed, Google Scholar, EBSCO-Host, and ProQuest according to the PRISMA 2009 guideline. We further assessed for risk of bias using SYRCLE’s risk of bias tool for preclinical studies and The Cochrane risk of bias assessment tool for the clinical studies. We used Review Manager (version 5.4) with random effect model to obtain a pooled mean difference with 95% CIs. Results: Five preclinical studies and three clinical studies were selected and pooled. The significant decrease in the level of Fasting Plasma Glucose (FPG), Fasting Insulin (FI), lipid profile, and Homeostatic Model of Insulin Resistance (HOMA-IR) value, and a significant increase in Quantitative Insulin-Sensitivity Check Index (QUICKI) value found in preclinical studies. The result for clinical studies showed a significantly decreased HOMA-IR values (SMD=-0.36, p=0.001), FPG level (SMD=-3.32, p=0.0001), Serum Insulin level (SMD=-1.47, p=0.002), and increased QUICKI value (SMD=0.01, p=0.006). Conclusion: Curcumin offers a substantial effect on metabolic disturbance parameters in PCOS patients and could be an alternative promising treatment for PCOS patients in the future.Pengaruh Kurkuma terhadap Parameter Gangguan Metabolik pada Pasien SOPK: Tinjauan Sistematis dan Meta-Analisis Uji Acak Preklinis dan Klinis TerkontrolAbstrakTujuan: Sindrom Ovarian Polikistik (PCOS) merupakan suatu kelainan ginekologi dan endokrin dengan gangguan metabolisme dan infertilitas sebagai konsekuensi jangka panjang yang paling umum ditemukan. Kurkumin muncul sebagai salah satu pengobatan herbal alternatif dalam pilihan terapi PCOS. Penelitian ini bertujuan untuk menyelidiki efek terapeutik kurkumin terhadap parameter gangguan metabolik pada pasien PCOS dan model tikus yang mengalami PCOS.Metode: Penelitian ini dilakukan dengan mencari studi penelitian yang memenuhi syarat menggunakan PubMed, Google Scholar, EBSCO-Host, dan ProQuest mengikuti PRISMA 2009. Penilaian risiko bias studi menggunakan SYRCLE’s Risk of Bias Tool untuk penelitian preklinis dan The Cochrane Risk of Bias Assessment Tool untuk penelitian klinis. Sintesis kuantitatifmenggunakan Review Manager (versi 5.4) dengan random effect model untuk mendapatkan pooled mean difference dengan interval kepercayaan 95%.Hasil: Sebanyak lima studi penelitian preklinis dan tiga studi penelitian klinis memenuhi kriteria. Terdapat penurunan signifikan kadar gula darah puasa, insulin puasa, profil lipid, dan nilai HOMA-IR, serta peningkatan nilai QUICKI pada studi preklinis. Pada studi klinis menunjukkan penurunan nilai HOMA-IR (SMD=-0,36, p=0,001), gula darah puasa (SMD=-3,32, p=0,0001), insulin serum (SMD=-1,47, p=0,002), dan peningkatan nilai QUICKI (SMD=0,01, p=0,006).Kesimpulan: Curcumin dapat memberikan efek terapeutik terhadap parameter gangguan metabolik pasien PCOS dan menjadi salah satu tatalaksana alternatif pasien PCOS di masa depan.Kata kunci: kurkuma; gula darah puasa; sindrom ovarium polikistik.